History Can Be Open Source: Democratic Dreams and the Rise of Digital History. - Locke, Joseph L.; Wright, Ben (American Historical Review, 2021)
In an ongoing commitment to experimentation, the AHR invited an "open peer review" of a submitted manuscript, "History Can Be Open Source: Democratic Dreams and the Rise of Digital History," by Joseph L. Locke (University of Houston–Victoria) and Ben Wright (University of Texas at Dallas). Given that Locke and Wright argued for the coexistence of transparency alongside formal academic peer review, subjecting their submission to an open review made sense. The peer review process itself tested the propositions about the democratization of scholarship they put forth in their submission. Their article appears in a new section of the AHR , "Writing History in a Digital Age," overseen by consulting editor Lara Putnam (https://ahropenreview.com/). The maturation of digital history has propelled historians' embrace of open educational resources. But, this article argues, open access licensing is not enough. Digital history's earliest practitioners promised not just more accessible digital materials, but a broader democratization of history itself. This article therefore moves beyond questions of technological innovation and digital access in the rise of digital history to engage more fundamental and intractable questions about inequality, community, and participatory historical inquiry.